2023
DOI: 10.1021/acs.inorgchem.2c04076
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-Inspired Two-Dimensional Halide Perovskite Facilitated Dopamine Polymerization and Self-Adhesive Photoelectric Coating

Abstract: Polydopamine (PDA) is a good adhesion agent for lots of gels inspired by the mussel, whereas hybrid organic–inorganic perovskites (HOIPs) usually exhibit extraordinary optoelectronic performance. Herein, mussel-inspired chemistry has been integrated with two-dimensional HOIPs first, leading to the preparation of new crystal (HDA)2PbBr4 (1) (DA = dopamine). The organic cation dopamine can be introduced into PDA resulting in a thin film of (HPDA)2PbBr4 (PDA-1). The dissolved inorganic components of layered perov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Their first decomposition starts at 280 °C with a weight loss around 57%, which might be attributed to the volatilization of two (C 8 H 12 NO 2 )Br per formula (56.06% in theory for 1 ). 27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their first decomposition starts at 280 °C with a weight loss around 57%, which might be attributed to the volatilization of two (C 8 H 12 NO 2 )Br per formula (56.06% in theory for 1 ). 27…”
Section: Resultsmentioning
confidence: 99%
“…The cation can be polymerized resulting in a self-adhesive photoelectric coating (HPDA) 2 PbBr 4 . 27 Through doping, (HDA) 2 PbBr 4 is expected to have richer optical properties, further facilitating interdisciplinary research.…”
Section: Introductionmentioning
confidence: 99%
“…15 Furthermore, Wu et al reported a cis-bis(2-phenylpyridine) platinum(II) complex (Pt( ppy) 2 ), which was produced by a one-pot method. 16 This complex showed intensive red and deep-red phosphorescence with lifetimes longer than 1.92 μs and quantum yields higher than 70%. It was used in the fabrication of electroluminescent (EL) devices and for cell imaging.…”
Section: Introductionmentioning
confidence: 97%
“…34 Type one contains a bidentate ligand and two monodentate ligands. 35 Type two contains two bidentate ligands 16 and type three contains a tridentate ligand and a monodentate ligand. 36 Furthermore, type four contains four monodentate ligands and type five contains one single tetradentate ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Halide perovskites have become a research hotspot in fields such as chemistry, physics, and materials due to their excellent photoelectric properties, including long carrier diffusion lengths, low trap densities, tunable band gaps, and high photoluminescence quantum yields (PLQYs). According to their structural connectivity, perovskites can be classified into zero-dimensional (0D), one-dimensional, two-dimensional, and three-dimensional. 0D halide perovskites with isolated metal halide octahedra have received widespread attention due to their efficient broadband emission attributed to self-trapped exciton (STE) emission. , On the other hand, 0D halide perovskites can adopt various organic cation and guest metal ions, which can tune emissions as desired. …”
Section: Introductionmentioning
confidence: 99%